Tracing anxious politics in Amsterdam. (14th March 2016) - de Koning, Anouk
ABSTRACT: In recent decades the Netherlands has seen the rise of anxieties regarding the present and future of the nation. De Koning explores the way such anxieties circulate and are taken up in various settings and by differently positioned people, using the 'notorious' Amsterdam Diamantbuurt neighbourhood as her vantage point. She focuses on engagements with the iconic figure of the troublesome 'Moroccan youth' in order to trace how such anxious discourses move from the national stage, to the neighbourhood and into the narratives of Moroccan-Dutch residents. While younger women contest discourses that frame their male peers as inherently disposed to crime, and instead single out overzealous policing, older residents grapple with explanations. They articulate an anxious belonging that differs markedly from the contentious narratives of the younger generation. These engagements give us a sense of how such publicly articulated anxieties interpellate differently positioned people, and feed into generationally specific senses of belonging.